ANOMALI MEDAN GRAVITASI PERMUKAAN (G) AKIBAT GERHANA MATAHARI SEBAGIAN (GMS) 9 MARET 2016 MENGGUNAKAN ANALISIS TRACKER PADA KATERâ€™S REVERSIBLE PENDULUM - Sholihat, Fitri Nurul; Ramayanti, Suci; Setyadin, Anggi Hanif; Ferahenki, Ardi Rizkia; Nugraha, Muhamad Gina; Saepuzaman, Duden; Samsudin, Achmad; Utama, Judhistira Aria; Susanti, Hana; Kirana, Kartika Hajar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study was conducted to determine the gravitational field of the Earth’s surface anomaly (g) due to the partial solar eclipse. Large gravity field of Earth’s surface can be obtained using a pendulum swing period. Data were collected for three days on 8, 9, and 10 March, 2016 from at 6:00 to 9:00 pm in Bandung with coordinates 6Â°51’48 " LS, 107Â°35’40" BT. The tools used in this research was Kater’s reversible pendulum with a deviation of less than 3Â° so that the motion can be regarded swing harmonics. Pendulum swinging motion is recorded using high resolution cameras (High definition) with a shooting speed 24 of frames per second (fps), the video is analyzed using the tracker in order to obtain the period of a pendulum swing. The results show the value of the gravitational field of the Earth’s surface on a three-day consecutive sampling of 10,33153834, 10,18560435, and 10,32046468. According to the research there are anomalies in the gravitational field of the Earth’s surface (g) due to the partial solar eclipse with the value of the gravitational field which decreases the time of the eclipse. Keywords: Eclipse, Tracker, Katerâ€™s Reversible Pendulum.